Gel casting of mullite for radome applications. Issue 1 (22nd May 2019) - Ecebaş, Nazım; Dursun, Gülsüm Meryem; Yeşilova, Aysu Hande; Duran, Cihangir
Abstract: Gel‐casting method was used to fabricate mullite ceramics because this method has not been applied to fabricate dense mullite in literature. Gel‐casting parameters such as monomer types (acrylamide and metyhlenebisacrylamide), effect of initiator (ammonium persulfate), and catalyst (tetramethylenediamine) were studied. All samples reached to relative densities of 97% to 98.2% after sintering at 1540°C for 2 hours. Backscattered SEM images revealed anisotropically grown mullite grains, glassy phase located at triple junctions, hexagonally‐shaped and faceted Al2 O3 grains, and white‐color grains consisting of ZrO2 and undissolved TiO2 . A Weibull modulus of 12.33 (ie, indicating tough ceramics) and characteristic strength of 186 MPa were calculated, below which no failure was expected. A critical quenching temperature was found as about 400°C (Δ T  ~ 380°C) by indentation‐quench method. In addition, a thermal shock resistance parameter (eg, R in °C) of 142.4°C was calculated, which was higher than commonly used Al2 O3 ceramics. Lower dielectric constant and loss are desired for wide frequency band application and shorter signal transmission delay time in radomes. The dielectric constant was found as nearly 7.5 up to 10 GHz and loss tangent was 0.0031 at 5 MHz. Dielectric and thermomechanical results suggest that mullite is a suitable candidate ceramic for radome applications.